(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study evaluates the Pangkabuhayn Qcitizens program to the vendors of Commonwealth market, Quezon City, in terms of financial stability, business stability, and their problem encounters to avail of the financial assistance business program. The results of this study show that the evaluation of financial assistance programs is “Relatively stable” in terms of financial stability, business stability, and other business sources. They have their own capability how to improve their business using the financial assistance business program; the problem encountered to availed financial assistance business program is they don’t have the ability to get the Quezon city identification (I.D) The study recommended that the financial assistance business program of Mayor Joy Belmonte in Quezon City is will they continue to provide and give financial assistance business program to every vendor on the sidewalk who needs it because they lose their profit and their income to support their family needs.